Digitalisasi Sistem Informasi Pelaporan Key Performance Indicator dengan Bantuan Dashboard untuk Jabatan Kepala Filling Station di Divisi Retail PT X - Seong Uook (Jurnal Titra, 2021)
Company always try to thrive for their business. One of the indicator to measure growth and achievement by using Key Performance Indicator (KPI). PT. X, the biggest industrial gases company in Indonesia, have applied KPI assessment for each quarter in a year. In this case, it will focused on the retail division that consists of filling station that being managed by branch manager. The problem with the present reporting information system for KPI assessment are done manually using excel. This will cause the assessment are wrongly calculated and it will affect their performance as Branch manager in filling station. The other problem is media to inform the result of KPI assessment not being visualized with interactive and related into each other in one single pane. These problem can be solve by proposing reporting information system to present achievement on KPI with dashboard. Feature that being used in this information system are from Google Workspace such as Google Spreadsheet and also an app to build dashboard which is Microsoft Power BI. This proposed information system on KPI assessment can simplify company to evaluate filling station performance and take a strategy move to keep thriving and compete with the other companies.